2008
DOI: 10.1086/588490
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Temperature Influences Diet Selection and Physiology of an Herbivorous Mammal, Neotoma albigula

Abstract: The whitethroat woodrat (Neotoma albigula) eats juniper (Juniperus monosperma), but the amount of juniper in its diet varies seasonally. We tested whether changes in juniper consumption are due to changes in ambient temperature and what the physiological consequences of consuming plant secondary compounds (PSCs) at different ambient temperatures might be. Woodrats were acclimated to either 20ЊC or 28ЊC. Later, they were given two diets to choose from (50% juniper and a nontoxic control) for 7 d. Food intake, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…We collected 21 animals from the Mojave Desert near Beaver Dam, Utah The two temperature treatments were 'cool' (218C) and 'warm' (298C). As in our previous studies [5,14], these temperatures were selected to be within the thermal neutral zone (298C) or just below this zone (218C) for N. lepida (see electronic supplementary material, figure S1). The temperatures are commonly experienced by animals in the Mojave Desert for up to six months of the year based on monthly mean and daily maximum values (see the electronic supplementary materials).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected 21 animals from the Mojave Desert near Beaver Dam, Utah The two temperature treatments were 'cool' (218C) and 'warm' (298C). As in our previous studies [5,14], these temperatures were selected to be within the thermal neutral zone (298C) or just below this zone (218C) for N. lepida (see electronic supplementary material, figure S1). The temperatures are commonly experienced by animals in the Mojave Desert for up to six months of the year based on monthly mean and daily maximum values (see the electronic supplementary materials).…”
Section: Methodsmentioning
confidence: 99%
“…Agricultural scientists have documented that a deleterious condition in cattle known as fescue toxicosis, caused by fungal toxins in infected grasses, was exacerbated at warmer temperatures [4]. Lastly, ecologists have shown that herbivorous rodents experienced temperature-mediated changes in the selection of diets containing plant secondary compounds [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in body temperature alter metabolic rate, rates of water loss, amounts and ratios of nutrients required, and tolerance to toxins and diseases. Hence, a decrease in ambient temperature results in rats increasing carbohydrate or fat consumption but not changing their protein intake (Aubert et al 1995), and changes in temperature affect tolerance of white-throated woodrats to plant secondary metabolites (Dearing et al 2008). Miller et al (2009) showed that locusts developed faster but converted protein and carbohydrate less efficiently to growth if kept at 38 C rather than at 32 C. If given a choice of temperatures under conditions of food abundance, locusts selected 38 C, therefore prioritising development rate over utilisation efficiency.…”
Section: Incorporating Abiotic Factorsmentioning
confidence: 99%
“…To add to dietary complexity, feeding by herbivores can influence the concentration and distribution of both chemicals and nutrients. Environmental conditions that change over short (e.g., seasons) and longtime periods (e.g., global climate change) can also influence concentrations of PSMs (Bidart-Bouzat and Imeh-Nathaniel, 2008;Lindroth, 2010) as well as toxicity of PSMs (Dearing, 2012;Dearing et al, 2008). In some cases, changes in concentration of PSMs may differ between terrestrial and aquatic systems.…”
Section: Pharmacological Mechanismsmentioning
confidence: 99%